Company Analysis: Leadership Styles and Rewards That Impact on Financial Performance - Yayan Rudianto; Erna Rusmiwati; Dyah Ciptaning L. S. Wardhani (Majalah Bisnis & IPTEK, 2023)
The purpose of this research is to examine how top management applies leadership and provides appropriate rewards to employee styles during the COVID-19 pandemic and endemic, as well as the impact on the company's financial performance. The research method used is descriptive quantitative, which is based on the philosophy of positivism. The population in this study were all employees of the Asep Stroberi Restaurant from its 11 branches, namely 396 employees. The research sample was all employees at Asep Stroberi Restaurant Ciawi Tasikmalaya, with a total of 36 employees. The results of the study found that financial leadership style has a positive impact on performance, while rewards on financial performance have a negative impact, which means that if there are too many rewards, financial performance will be disrupted or not good enough. This research can be taken into consideration by top management before giving rewards to employees, as a record of financial conditions before giving rewards.